Yoghurt sinbiotik ekstrak kulit buah naga merah (Hylocereus polyrhizus) dengan penambahan gula merah sebagai imunitas tubuh pada masa pandemi covid-19 - Siti Maisaro; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Yoghurt is a dairy product from the second fermentation of Lactic Acid Bacteria (LAB) as a starter, namely Streptococcus thermophilus and Lactobacillus bulgaricus which live in symbiosis. Lactic acid bacteria are bacteria that are capable of producing lactic acid, hydrogen peroxide, antimicrobials and other metabolic products that have a positive effect on health and the body at low environmental pH. Red dragon fruit (Hylocereus polyrhizus) contains higher levels of vitamin C, vitamin B3 (niacin), fiber and betacyanin than white dragon fruit. Dragon fruit skin which weighs 30-35% of the weight of the fruit has not been widely used by the general public and is only disposed of as garbage, thereby increasing environmental pollution. This study aims to determine the proportion of addition of dragon fruit peel extract and brown sugar to the best chemical, physical, and organoleptic quality in yogurt. The method used in this research is a factorial randomized block design (RAK) consisting of 2 factors, namely the proportion of addition of red dragon fruit peel extract (50 grams and 70 grams) and the addition of brown sugar (15 grams, 25 grams, and 35 grams). Each treatment was repeated 3 times to obtain 18 trials. The best research results on yogurt on chemical, physical, and organoleptic content were found in the B2G3 treatment (Addition of 70 grams of dragon fruit peel extract and 35 grams of brown sugar) with a protein value of 0.37%, viscosity 2.00 Pa.s, reducing sugar 4 .16 (mg/g), color with a value of 3.8 (like), aroma with a value of 3.4 (somewhat like), texture with a value of 3.1 (somewhat like), and taste with a value of 3.96 (like) .